Metagenomic analysis of goat feces from Ogliastra (Sardinia, Italy) - Monica Rosaria Molotzu; Piera Angela Cabras; Lisa Di Marcantonio; Rossano Atzeni; Nicolò Pietro Paolo Macciotta; Antonella Canu (Frontiers in Microbiomes)
With its constitutive and functional characteristics, the intestinal microbiota plays a crucial role in the health condition of the animals. Variations in the composition and gene expression of the intestinal microbiota are associated with the risk of the onset of various pathologies of the gastrointestinal tract and chronic inflammatory intestinal diseases. The objectives of this study were to evaluate the variability in the composition of the intestinal microbiota of goats of different breeds (Sarda, Maltese, and Alpine) farmed in different flocks of the region of Ogliastra (Sardegna, Italy) and to assess whether the type of feeding (natural pasture grazing-based versus intensive) could affect the intestinal bacterial composition. We also evaluated possible differences in the composition of the intestinal microbiota between healthy and Caprine arthritis encephalitis (CAE)-affected goats. The economic damage caused by this pathology is due to the reduction in milk production, with infected animals having greater susceptibility to contract diseases. The results of our study highlighted a statistically significant difference (P = 0.001–0.005) in the intestinal bacterial composition between the intensively managed flock and the other natural pasture-based flock.g In particular, a significantly greater abundance of Acidoaminococcaceae in the intensive flock was obgserved. Furthermore, a significantly greater abundance of Prevotellaceae was found in two localities in which, out of a total of 29 animals, only four tested negative for CAE. From these data, we deduced that the presence of Prevotellaceae can be an indication of the disease. This difference could be attributed to the farming system, the Cardedu farm being the only intensive one, and to the geographical distance of this location from the other sampling sites. Therefore, the results of the present study suggest that extensive or intensive farm management may affect the intestinal microbiota of goats.